MANAJEMEN KONTEN PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MIN 11 HULU SUNGAI UTARA - M. Akmal Rasyid; M. Salman, Maulana Basir, Muhammad Al Farid, Syahrani (CV. ADIBA AISHA AMIRA, 2025)
This research investigates the use of interactive content as a technology-based learning media tool to increase student learning motivation. In the context of rapid development of information and communication technology, education requires innovation in learning methods. Interactive content is recognized as an effective tool that can enrich students' learning experiences through clear and interactive visual representations. The aim of the research is to analyze literature related to student learning motivation, explore the benefits and challenges associated with it, and communicate the contribution of this research in the development of innovative learning practices. a research approach that uses data in the form of numbers to measure, analyze and interpret phenomena. It is used in a variety of scientific disciplines to identify relationships between variables, collect data with methods such as surveys or experiments, and produce findings that can be generalized to a larger population. Nonetheless, it is important for educators and researchers to pay attention to quality animation design as well as the role of educators in facilitates the effective use of animation. This research contributes to the development of innovative learning practices and further explores the use of animation as an effective learning medium in increasing student learning motivation.